Contained Morcellation: Review of Current Methods and Future Directions - Taylan, Enes; Sahin, Cagdas; Zeybek, Burak; Akdemir, Ali (Frontiers in Surgery, 2017)
Power morcellation of surgical specimen during laparoscopic surgery is a practical technology that provides the opportunity to perform several minimally invasive procedures. However, this technology brought forward additional risks and complications associated with dissemination of both benign and malignant tissues inside the abdominal cavity. Based on startling cases FDA announced a discouraging statement on the use of power morcellators that decreased the number of minimally invasive approaches in the following period. As a response to these concerns and negative impacts of the FDA statement, researchers developed several new approaches resulted in contained or in-bag morcellation methods. In this review we aimed to discuss these current methods and provide an insight for future developments.